BABRONE: A Comprehensive Database of Biotechnology and Bioinformatics Resources of North East India - Sarkar, Manas; Borah, Probodh (International Journal of Information Studies, 2025)
Biotechnology and Bioinformatics Resources of North East India (BABRONE) is the maiden approach to bring all the available information relating to these resources in a single platform. Till now profiles of 901 scientists have been included in the database. The profiles include details about their contact address, academic qualifications, working experience, research contributions and resources created. Detailed profile of all the universities, research institutes and colleges of the region are also listed in BABRONE, including GIS coordinates (longitude and latitude positions) of the institutions. Besides the public users, all these data are expected to be a valuable resource for the funding agencies that will help them in decision making and the discussion forum developed under this project will help in development of collaboration among the scientists and students of the region.